2010
DOI: 10.7326/0003-4819-153-2-201007200-00008
|View full text |Cite
|
Sign up to set email alerts
|

Open Notes: Doctors and Patients Signing On

Abstract: Few patients read their doctors' notes, despite having the legal right to do so. As information technology makes medical records more accessible and society calls for greater transparency, patients' interest in reading their doctors' notes may increase. Inviting patients to review these notes could improve understanding of their health, foster productive communication, stimulate shared decision making, and ultimately lead to better outcomes. Yet, easy access to doctors' notes could have negative consequences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
168
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(177 citation statements)
references
References 19 publications
6
168
0
3
Order By: Relevance
“…[17][18][19][20] In brief, we learned that patients were enthusiastic about the experience and reported potentially important clinical benefits, such as improved recall and understanding of their care plan, improved adherence to their medications, and feeling more in control of their care. We found that doctors were surprised by how few patients appeared troubled by what they read and how little effect the intervention had on the PCPs' work lives.…”
Section: An Initial Foray Into Primary Carementioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] In brief, we learned that patients were enthusiastic about the experience and reported potentially important clinical benefits, such as improved recall and understanding of their care plan, improved adherence to their medications, and feeling more in control of their care. We found that doctors were surprised by how few patients appeared troubled by what they read and how little effect the intervention had on the PCPs' work lives.…”
Section: An Initial Foray Into Primary Carementioning
confidence: 99%
“…How will what clinicians write change, and can one record serve multiple audiences? 17 Can sharing notes reduce morbidity among family caregivers, particularly when their parents or partners near the end of life? How might open notes evolve for patients in a rehabilitation facility, in long-term care, and perhaps most importantly, for those ill at home?…”
Section: Exploring New Terrainmentioning
confidence: 99%
“…In 2010, OpenNotes, a pilot study of shared primary care notes, was rolled out across multiple institutions in the United States [4]. Over 100 primary care physicians and about 25,000 patients were enrolled in an observational study in which patients had real-time access to their record through a secure internet portal.…”
Section: An Increasing Number Of Patients Are Accessing Electronic Hementioning
confidence: 99%
“…However, research can also integrate the patient point of view with that of the clinician as it is executed in current health information systems. DelBanco et al [4,5] opened physician notes in an existing EHR as part of the Open Notes project to thousands of patients. Patients reported feeling more in control of their care and sharing the content of notes with others, with no significant increase to physician workload among the physicians volunteering for project.…”
mentioning
confidence: 99%